1305 Staff wellbeing and team morale during the Covid-19 pandemic at Birmingham children’s hospital - Lee, Natasha (Archives of disease in childhood, 2021)
BackgroundCovid-19 has significantly impacted the nations day-to-day life and inevitably affected the workplace too. The NHS has been under visible unprecedented stress and consequently staff have carried the burden. The general paediatricians at Birmingham Children’s Hospital wanted to understand how the medical staff felt they could be supported during this difficult timeObjectivesTo assess the wellbeing and team morale amongst medical staff within the General Paediatrics team at Birmingham Children’s Hospital (BCH) during the Covid-19 pandemic and implement a new method to improve wellbeing and team morale.MethodsA questionnaire was created and distributed to the medical staff working within the General Paediatrics team at BCH. Questions were formulated following research relating to existing staff wellbeing questionnaires and current literature regarding the effects of Covid-19 on mental health, wellbeing and team morale.ResultsTwenty-two staff members completed the questionnaire which represented their experience over the last month. Fifteen (68.2%) looked forward to going to work and nineteen reported feeling ‘happy, smiling and laughing at work’ when asked. However, 27.3% only felt appreciated at work a few times a month or less and 31.7% stated that their good work was acknowledged less than a few times a month. Twelve felt that they needed someone to talk to at work and four felt unable to confide in a colleague at least a few times a month. 50% felt then needed some time alone during a break at work. 81.8% admitted that Covid-19 had affected their mental health or wellbeing, 50% felt socially isolated as a result of Covid-19 and 95.5% felt worried about their health of the health of family/friends as a result of Covid-19. Seventeen staff members felt that Covid-19 had affected team morale and eighteen felt that knowing their colleagues better would improve team morale and make them more likely to confide in them if needed.ConclusionsThis evaluation highlights that the majority of staff at BCH felt Covid-19 had affected their mental health, wellbeing and the General Paediatric team morale. It stressed the importance building colleague relationships to support each other during this worrisome time. A ‘Let’s Strike Up a Conversation’ matchbox activity was created in response to the findings to initiate non-covid and work-related conversation during work breaks. The matchbox had conversation starting ‘Match cards’ within to stimulate and improve team communications and encourage staff to get to know each other. The effects of this intervention are to be evaluated in due course. The assessment of staff wellbeing and team morale has highlighted the importance of actively surveying the team during new and unexpected changes/circumstances. Early recognition facilitates early response and adjustments to boost team morale and wellbeing.